2016
DOI: 10.3389/fpls.2016.00174
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Characterization of Gnetum parvifolium Reveals Candidate Genes Involved in Important Secondary Metabolic Pathways of Flavonoids and Stilbenoids

Abstract: Gnetum is a small, unique group of Gnetophyta with a controversial phylogenetic position. Gnetum parvifolium is an important Chinese traditional medicinal plant, which is rich in bioactive compounds such as flavonoids and stilbenoids. These compounds provide significant medicinal effects, mostly as antioxidant, anticancer, and antibacterial agents. However, the mechanisms involved in the biosynthesis and regulation of these compounds in G. parvifolium are still unknown. In this study, we found that flavonoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 48 publications
(64 reference statements)
0
42
0
Order By: Relevance
“…Transcriptomic analyses can be used to identify functional elements in the genome, metabolic pathways, and differentially expressed genes in model and non-model organisms [17][18][19][20]. The transcriptomes of many important medicinal plants and their individual tissues such as leaves, roots, and stems have been reported [21][22][23][24][25]. Genomic resources and transcriptome sequences for German chamomile and Roman chamomile are very limited at present, and the complex regulatory mechanisms that control carbon flux through the terpenoid biosynthetic pathway and their cooperation in the biosynthesis of volatile terpenoids remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analyses can be used to identify functional elements in the genome, metabolic pathways, and differentially expressed genes in model and non-model organisms [17][18][19][20]. The transcriptomes of many important medicinal plants and their individual tissues such as leaves, roots, and stems have been reported [21][22][23][24][25]. Genomic resources and transcriptome sequences for German chamomile and Roman chamomile are very limited at present, and the complex regulatory mechanisms that control carbon flux through the terpenoid biosynthetic pathway and their cooperation in the biosynthesis of volatile terpenoids remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Using LC-QTOF-MS-based metabolite profiling, Degu et al (2016) demonstrated that high light treatment (2500 lmol m -2 s -1 ) applied to detached Shiraz grape berries led to a transient increase in stilbene levels at pre-veraison (piceid) and veraison (piceid and viniferin) stages, while high temperature (40°C) specifically induced viniferin content at all sampling times only at the pre-veraison stage. Recent results obtained by Deng et al (2016) showed that high temperature (40°C) induced expression of the PAL-, C4H-, 4CL-, and STS-like genes and increased piceatannol levels in the leaves of Gnetum parvifolium, but did not affect resveratrol levels. However, the following analysis revealed that the high temperature conditions inhibited the accumulation of both resveratrol and piceatannol in G. parvifolium stems and roots, while expression of the stilbene biosynthesis genes was increased with some variability (Deng et al 2017).…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…Multiple studies show that UV-C light exposure induced stilbene biosynthesis in different plant species (e.g., grapevine, pine, peanut, and gnetum), and the induction was accompanied by a transcriptional activation, protein accumulation, and enzyme activation of STS and some other stilbene biosynthesis enzymes (Wang et al 2010Tang et al 2010;Suzuki et al 2015;Deng et al 2016Deng et al , 2017Kiselev et al 2017). For grapevine berries, it has been shown that the induction of resveratrol biosynthesis after UV-C irradiation occurred primarily in the form of t-resveratrol (not piceids) and was dependent on the berry developmental stage .…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…2a, a total of 76 744 (46.98%) unigenes were successfully annotated in at least one database, 9074 (5.55%) were annotated in all databases, and 86 596 unigenes (53.02%) were not annotated in the public databases chosen in this study. The low rate of annotation may be attributed to the limited genomic information available for Z. bungeanum or because most of unannotated unigenes were too short to generate a blast hit and the same results also appeared in the transcriptomes of Carya illinoinensis 32 , Pseudostellaria heterophylla 12 , and G. parvifolium 15 which were constructed of several libraries and generated many unigenes. Additionally, species distribution analysis based on blast hits against the non-redundant database showed that Citrus sinensis and Citrus clementine were the top-hit species, which are in the same evolutionary unit as Rutaceae with Z. bungeanum 33 , and accounted for 64.83% (34 631) of the identified unigenes.…”
Section: Unigene Annotation and Functional Classificationmentioning
confidence: 99%
“…To screen and identify the pathways and genes related to the biosynthesis of secondary metabolites, RNA-seq based on high-throughput sequencing technology is a cost-effective and powerful tool to obtain many transcripts from different tissues or the same tissue from different developmental stages, which can be used for differentially expressed gene (DEG) analysis combined with Gene Ontology (GO) classification and Kyoto Encyclopedia of genes and Genomes (KEGG) pathway functional enrichment analysis to identify key genes [12][13][14] . For example, pathways and genes involved in the production of secondary metabolites, such as flavonoid and stil-benoid biosynthesis in Gnetum parvifolium 15 , terpenoid and thenylpropanoid biosynthesis in Ananas comosus 16 and caffeine and theanine biosynthesis in Camellia sinensis 17 have been verified by comparative transcriptome sequencing.…”
Section: Introductionmentioning
confidence: 99%